Expression Studies of the Cancer Drug and Its Effect on Angiogenesis-Promoting Genes in Cancer Cell Lines - Salam Abbas1 , Noor Harith AL-Hamid (Indian Journal of Forensic Medicine & Toxicology, 2020)
Objective: Being a member of RNA binding proteins, Human Antigen R (HuR) is considered as an acutefactor to mediate the proangiogenic factors causing the angiogenesis amongst tumor cells. All through theanoxic conditions and inflammation, the cytokine IL-1 activated the HuR which further downregulated orupregulated the hypoxia inducible factors (HIF1?). Current study was conducted to observe the correlativeimpact of Decetexal (Taxotere) cancer drug on HIF? and HuR expression levels while utilizing the cell lineHeLa.